The Glenbuchat ballads - Scott, Robert, 1788-1855; Buchan, David, 1939-; Moreira, James, 1956- (University Press of Mississippi in association with the Elphinstone Institute, University of Aberdeen, Scotland, 2007)
Sometime in the early nineteenth century, most likely in the year 1818, the Reverend Robert Scott, minister of the parish of Glenbuchat in Aberdeenshire, Scotland, compiled a collection of traditional ballads that until now has not been published. Most of the ballad collections produced during the Scottish Romantic Revival were eventually anthologized in Francis James Child's seminal English and Scottish Popular Ballads (five volumes, 1882-96). Yet, the Glenbuchat manuscripts, containing sixty-eight ballads in four folio volumes, were not included in Child's volumes. The complete work only cam.